Strategic Positioning Behavior and the Inter-Granger-Causality of Alternative Securities Investments in Thailand: A Study - Nasution, Eric J. de Sera (Human Behavior, Development and Society, 2024)
In this study the strategic positioning behavior of Thai investors from 1997 to 2022 was evaluated in order to explore the deterministic variables of why they might prefer to invest in either money markets or mutual funds/bonds, relative to equity market investments. Using factor analysis and publicly available financial data to answer these questions, it was discovered that attractive yields and the tradeoff of risk-return were essential factors that led to such investment behavior. Using a cointegration Autoregressive Distributed Lag method, an Error Correction Model, and Granger causality to verify these findings, dividend yield and risk-return tradeoff were the only predicted causes. The multiplier effects of marginal propensity to invest and equity market investment turnover in Thailand are catching up in terms of economic development in other Association of Southeast Asian Nations. These findings point to a need for further innovative development of Thai equity and alternative investment markets.